The Influence of Transformational Leadership, Employee Competence and Work Ethic on Employee Performance Mediated by Innovative Work Behavior : Pengaruh Kepemimpinan Transformasional, Kompetensi Pegawai Dan Etos Kerja Terhadap Kinerja Pegawai Yang Dimediasi Oleh Innovative Work Behavior - Riskha Nuranti; Kusiyah Kusiyah; Dasih Irma Istiatik (OGZ Research & Publishing, 2026)
Objective : This study aims to analyze the influence of transformational leadership, employee competence, and work ethic on employee performance, mediated by innovative work behavior, at the Pasar Rebo Subdistrict Office, East Jakarta. Methods : The research employed a survey method using questionnaires distributed to 68 employees selected through total sampling. Data were analyzed using Structural Equation Modeling (SEM) with Smart PLS 4 software. Results : The findings reveal that transformational leadership and work ethic significantly affect innovative work behavior, while employee competence does not. Innovative work behavior, in turn, does not influence employee performance. Furthermore, transformational leadership and employee competence show no direct effect on employee performance, whereas work ethic does. Additionally, innovative work behavior does not mediate the relationship between transformational leadership, competence, or work ethic and employee performance.